PENGARUH GAYA BELAJAR VISUAL TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN FIQIH DI MADRASAH ALIYAH NEGERI TANJUNGPINANG - Amir Husin; Hernawati; Milasari; Rofiatul Adania (STAI Miftahul Ulum Tanjungpinang, 2023)
The purpose of this study was to answer 3 problems, namely: (1) How is the visual learning style of class X students in Fiqh subjects at Madrasah Aliyah Tanjungpinang State; (2) How are the learning outcomes of class X students in fiqh subjects at Madrasah Aliyah, Tanjung Pinang; (3) Is there any effect of students' visual learning styles on student learning outcomes in fiqh subjects at Madrasah Aliyah, Tanjung Pinang. This study aims to (1) determine the visual learning style of class X students in fiqh subjects at Madrasah Aliyah Tanjungpinang State; (2) Knowing the learning outcomes of class X students in fiqh subjects at Madrasah Aliyah Tanjungpinang State; (3) Knowing the effect of students' visual learning styles on Fiqh subjects on the learning outcomes of class X students at Madrasah Aliyah Tanjungpinang State. In this study, the technique used by researchers in collecting data is using questionnaires, interviews, documentation and observation. The conclusion of this research is that the students' visual learning style reaches 85.6%. This is evident from the results of the questionnaire data on variable X which is in the range of 81% - 100% categorized as Very Good. Student learning outcomes reached 82.3%. This is evident from the results of the Y variable questionnaire data which is in the range of 81% - 100% categorized as Very Good. The Pearson correlation number is **0.468, which means that the correlation between students' visual learning style variables and student learning outcomes is 0.468. The Pearson correlation value is 0.468, so it can be concluded that the degree of relationship between the Pearson correlation values ​​is at 0.40 – 0.70, which means that the X and Y variables are sufficiently correlated. Then the relationship between variables X and Y is positively related. This means that 46.8% of student learning outcomes are influenced by variable (X), while the remaining 53.2% is influenced by other variables not examined in this study.